The Services Sector in the Dutch Economy: Economic Contribution and External Trade Performance - Saoud, Wassilla; Hani, Mohamed (Oeconomica Jadertina, 2026)
This study aims to present the structural dynamics and the contribution of the services sector to the Dutch economy, as one of the European Union countries that serves as a leading model for service-based economies. A descriptive-analytical approach was used to analyse official Eurostat statistics on the services sector for the period 2010-2020, while trade in services data extend to 2024. Results reveal that the services sector plays a pivotal role within the Dutch economy, contributing significantly to value creation, profitability, and foreign trade, including exports and imports. Despite its flexibility and diversity, the services sector remains vulnerable to global fluctuations, emphasizing the need for strategic investment and policy support to maintain competitiveness and long-term growth. This study is limited by the absence of 2017 data for the services sector, and the small sample size used in the regression models. The contribution of this study lies in providing a uantitative analysis that complements previous qualitative studies and sheds light on its role in the Dutch economy and international trade. More comprehensive future research, in terms of both data and period, could be recommended, including a study of the impact of global factors on the service sector in the Netherlands, or a comparison with specific countries.